A Study of Iraqi EFL Learners’ Misuse of Repetition as an Emphatic or Redundant Process in Translation - Fenjan , Lecturer: Sahab Salih (Thi Qar Arts Journal, 2022)
Recently, translation studies have received more attention on translation efficiency and the correct use of repetition in the translation process to know what translator’s skills are important in order to achieve a qualified and precise translation. The current study aims to investigate the misuse of repetition as an emphatic or redundant process in translation by EFL learners, especially the Iraqi university EFL students. The study sample consisted of 30 randomly selected fe/male students at the department of English language majoring in translation or English language literature of University of Thi-Qar. A researcher’s designed test has been administered to the Iraqi EFL learners and their responses have been descriptively analyzed. The study is dealt with four sections to discuss and find the precise results of the planned aims. So, the first section presents introduction, problem statement, research questions, objects, and research significance. The second section deals with the literature review to expose theoretical background of translation, repetition, redundancy, and related studies. The third section is about research method and design. Whereas, the fourth section exposes the results and discussions where it is found that the Iraqi university EFL students have a low level of awareness of translation skills and low performance regarding the use of repetition in their translation process which can be referred to their insufficient lexical knowledge in both target and source languages. Furthermore, the results also showed that a large part of the EFL students was able to distinguish the repeated terms, however they do not realize the reason or the purpose of the correct use of the emphatic repetition as a tool that contributes to creating lexical coherence in texts. The study concluded that there are many causes of the misusing forms of repetition in translation, including the students’ weak ability to translate abbreviations and their inability to find suitable synonyms for Arabic words to be used in English translation. These major causes point to the urgent need for systematic reforms of the curriculum, methods of teaching EFL in universities, and strategies adopted for teaching translation to students. An appendix of the test is found at the end of the research.